2008
DOI: 10.1021/ja803658n
|View full text |Cite
|
Sign up to set email alerts
|

Deracemization of a Dynamic Combinatorial Library Induced by (−)-Cytidine and (−)-2-Thiocytidine

Abstract: A dynamic combinatorial library composed of racemic hydrazone-based dipeptides becomes deracemized on binding to the chiral analytes (-)-cytidine and (-)-2-thiocytidine through the amplification of two receptors, (SS)-dimer and (RRRR)-tetramer. The deracemization phenomenon was investigated by laser polarimetry, mass-tagged pseudo-enantiomers in conjunction with electrospray ionization mass spectrometry, HPLC/UV-MS, UPLC/UV-MS, rapid-resolution LC-MS, collision-induced dissociation MS/MS, and numerical simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 55 publications
1
18
0
Order By: Relevance
“…[6] The covalent argument is in accord with the molecular orbital description that two SOMOs overlap to form a bonding supermolecular orbital referring to a bonding electron pair in a covalent bond. [9,11,[15][16][17] This argument is illustrated in Figure 1 for the TCNE 2 2À anion radical dimer. The TCNE 2 2À dimer system is the smallest 2e-mc pancakebonded radical dimer and it serves well as a model system to understand pancake bonding.…”
Section: Introductionmentioning
confidence: 84%
“…[6] The covalent argument is in accord with the molecular orbital description that two SOMOs overlap to form a bonding supermolecular orbital referring to a bonding electron pair in a covalent bond. [9,11,[15][16][17] This argument is illustrated in Figure 1 for the TCNE 2 2À anion radical dimer. The TCNE 2 2À dimer system is the smallest 2e-mc pancakebonded radical dimer and it serves well as a model system to understand pancake bonding.…”
Section: Introductionmentioning
confidence: 84%
“…A DCL formed by the racemic BB 38 rendered a mixture of cyclic oligomers of different sizes [37] and bearing all the possible stereochemical combinations of chiral centers. Thus, the corresponding derace mization of the mixture amplified two different macrocyclic pseudopeptides: the (S,S)-dimer from (−)-cytidine while the (R,R,R,R)-tetramer from (−)-2-thiocytidine [39]. The HPLC analysis coupled with a laser polarimeter detec tor and complementary studies with isotopically labeled pseudoenantiomers confirmed that the amplified dimer had (S,S) configuration [38].…”
Section: Pseudopeptides In Dynamic Covalent Chemistrymentioning
confidence: 83%
“…LC -MS has been used by Gagn é et al in an elegant study showcasing some clever analytical chemistry for investigating chiral recognition in DCLs [11,12] . The authors screened a library made from a racemic hydrazide/aldehyde building block for binding to a chiral template using an optical rotation detector.…”
Section: Lc -Ms Analysismentioning
confidence: 99%
“…Application of DCLFit in experimental systems are now starting to appear [27,28] . For a smaller DCL a similar approach to determining binding constants has been reported making use of off -the -shelf software [12] .…”
Section: Quantifying Equilibrium Constantsmentioning
confidence: 99%